Tech-Enhanced Pedagogy: Transforming English Language Instruction - Gyawali, Yadu Prasad (American Journal of STEM Education, 2024)
This research explores innovative approaches to teaching English, particularly through the integration of information and communication technology (ICT) tools such as Mentimeter and Padlet. It observes how these tools augment student engagement and learning, specifically within the Critical and Creative Thinking Lab and Pedagogy of English courses in UITTR. This study underscores the significant influence of ICT on improving peer communication and collaboration, confirming the transformative impact of technology on education. The study highlights that the effectiveness of ICT in teaching is largely dependent on teachers’ digital competence, with significant variances observed across different regions. Through a qualitative participatory action research methodology, this study involved UITTR students and employed thematic analysis to uncover the challenges and benefits of ICT integration in the classroom. The findings reveal that Mentimeter and Padlet foster interactive and learner-friendly environments, promoting a paradigm shift toward more engaging and learner-centered English language instruction. The study concludes with a call for ongoing professional development to equip educators with the technical, pedagogical, and content knowledge required to harness the full potential of ICT in transforming pedagogical practices.